PROFIL USAHA INDUSTRI BAKERY PADA PERUSAHAAN â€œNEW SEGARâ€ DI KELURAHAN PINAESAAN KECAMATAN WENANG KOTA MANADO - Jonathan Armando Malonda; Welson M. Wangke; Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2018)
This study aims to describe the business profile of the bakery industry in the company "New Segar" in Pinaesaan Urban District Wenang Manado City. This research was conducted in January to March 2017. The data used are primary data and secondary data. This research is done by directinterview technique with company leader who holds authority and plays an important role in "New Segar" operational process. The data obtained were analyzed using descriptive analysis and presented in tabular form. The result of this research shows that the business profile of New Segarbakery industry is a cottage industry and has 8 manpower with production of 3 bread models as much as 4600 packs with production value Rp.48.300.000, for its marketing is done in Manado, Tomohon and Minahasa North. New Segar bakery business has gained profit in 1 month amounting to Rp.20.805.000.